Modeling the effects of radiation on the bone tumor microenvironment: opportunities for exploring combination therapies in microphysiologic systems - Kailey N. Jackett; Devin L. DaPonte; Pranav Soman; Jason A. Horton (Cellular & Molecular Biology Letters)
Abstract Primary bone tumors and bone metastases represent significant challenges in oncology. Radiotherapy is an important adjuvant treatment for several primary bone and musculoskeletal tumors, as well as for palliative care for metastatic bone lesions. While effective in these applications, patients receiving skeletal radiation face a lifelong risk of fragility fracture at the irradiated sites, among other complications. Damage to bone could be reduced by development of tumor-selective radiosensitizers that would enhance the efficacy of radiotherapy, resulting in reducing the radiation dose delivered to the normal tissues. The creation of bone-selective radioprotection and radio-mitigant strategies that could respectively reduce the magnitude of off-target damage and stimulate functional recovery of the healthy bone microenvironment are warranted. Key barriers to progress in this field include the paucity and inconsistency of data on the skeletal effects of radiotherapy, low throughput and high cost of animal models, reproducibility challenges with in vitro experiments, and poor translational relevance of these models, which may not accurately replicate the human bone-tumor microenvironment. Microphysiological systems (MPS) will accelerate progress in this field by enabling rapid and cost-effective investigation while recapitulating the complexity of the bone-tumor microenvironment to more accurately model the collective response to therapy. Here, we summarize the current knowledge on the transient and long-lasting impacts of radiotherapy and explore opportunities for MPS to streamline and expand our knowledge base. We critically evaluate contemporary model systems, including MPS, and offer suggestions for how these systems can be used to efficiently model the intersection of skeletal radiobiology and bone cancer, and accelerate development of combination therapies. Graphical Abstract